2019
DOI: 10.1039/c9cp01764j
|View full text |Cite
|
Sign up to set email alerts
|

Characterising glass transition temperatures and glass dynamics in mesoporous silica-based amorphous drugs

Abstract: Amorphous drug molecules bound to MPS surface are restricted in mobility, but they exhibit a primary glass transition temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…On the other hand, when the amount of drug was lower than the maximum loading of the drug, the Tg of the drug was not observed. Other studies reported that the Tg of the drug in the mesoporous silica would be changed due to the different mobility of amorphous drugs [26,27]. The Tg event of the RTV amorphous state in the weight ratio of RTV/MPS1 of above 4:6 and CYP amorphous state in the CYP/MPS1 = 5:5 was almost similar with the RTV amorphous and CYP amorphous states, respectively.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…On the other hand, when the amount of drug was lower than the maximum loading of the drug, the Tg of the drug was not observed. Other studies reported that the Tg of the drug in the mesoporous silica would be changed due to the different mobility of amorphous drugs [26,27]. The Tg event of the RTV amorphous state in the weight ratio of RTV/MPS1 of above 4:6 and CYP amorphous state in the CYP/MPS1 = 5:5 was almost similar with the RTV amorphous and CYP amorphous states, respectively.…”
Section: Discussionmentioning
confidence: 63%
“…However, other studies have reported that the molecular mobility of drugs loaded with small enough pores is significantly lower Pharmaceuticals 2022, 15, 93 3 of 16 than in bulk. This indicates the T g will be higher than the bulk amorphous [27,28]. On the other hand, the glass transition of the drug, which adsorbed monomolecularly on the silica surface, was not detected, as the monolayer of the drug on the silica surface does not contribute to the T g signal in the DSC.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The carbonyl group and phenyl rings of ritonavir also interact with the surface of MPS, as observed in the solid-state NMR experiment (Figure 3). The previous study also stated that the interaction of the drug with the MPS surface restricts their mobility and forms a monolayer [38][39][40]. The hydrogen bonding between the carbonyl group of RTV and the silanol group of MPS was also reported [34].…”
Section: Discussionmentioning
confidence: 94%
“…These findings were underscored by the absence of melting endotherms in the DSC thermograms of the silica-based formulations after 90 days [39]. By contrast, melting peaks were observed in both samples of the extruded formulations after 90 days, indicating the presence of drug crystallinity (data not shown).…”
Section: Resultsmentioning
confidence: 96%